Cattle rustling and insecurity in rural communities of Kaduna State, Nigeria: an empirical study - Abu Bakar, Mohammed Bashir; Yusof, Rohana; Talib, Azlizan (2018)
Existing data on the level and magnitudes of insecurity in rural communities, Nigeria discloses an increase over time, which creates serious threat to lives and properties, hampers business activities. This rising upsurge of insecurity led by cattle rustling has remained unabated nonetheless has assumed a dangerous dimension which is threatening the corporate being of the country as one geographical entity. This study is on the nature of cattle rustling and its consequences on security in the rural communities of Kaduna State. The study was empirical in nature, qualitative data were collected using in-depth interviews. Findings shows that cattle rustling has caused serious havoc in the rural communities in terms of loss of lives, psychological fear migration, and organised crime which culminated to insecurity. The study recommends that government responsiveness and co-opting community members in the security of the area will go a long way in solving the lingering insecurity in the study area